Influence of Autochthonous Lactic Acid Bacteria Cultures on the Microbiota and Biogenic Amine Production in Medium-Ripened Artisan Goat Cheese - Julia Mariano Caju de Oliveira; Adriane Elisabete Costa Antunes; Gustavo Felipe Correia Sales; Camila Neves Meireles Costa; Angela Matilde da Silva Alves; Kaíque Yago Gervazio de Lima; Celso José Bruno de Oliveira; Antônio Silvio do Egito; Karina Maria Olbrich dos Santos; Evandro Leite de Souza; Maria Teresa Bertoldo Pacheco; Maria Elieidy Gomes de Oliveira (Foods)
This study evaluated the effects of adding the autochthonous cultures Limosilactobacillus mucosae CNPC007 (LM) and Lactiplantibacillus plantarum CNPC003 (LP), originally isolated from goat milk and goat cheese, respectively, on microbiological safety, microbiota composition (analyzed through 16S rRNA gene metataxonomic sequencing), and biogenic amine (BA) production in artisanal goat (coalho) cheese made from raw or pasteurized milk during 60 days of ripening at 10 °C. Six types of cheese were produced, varying in milk treatment (raw or pasteurized) and the presence or absence of LP or LM cultures. Adding either LP or LM significantly modulated the microbiota, favoring Streptococcus dominance and reducing overall bacterial diversity compared to non-inoculated cheeses. Raw milk cheeses with added autochthonous cultures exhibited a microbial profile like pasteurized cheeses, suggesting a homogenizing effect on the microbiome. Both cultures effectively reduced microbial load in raw milk cheeses after 20 days, reaching levels comparable to pasteurized cheeses by the end of ripening. Although BA concentrations increased over time, all samples remained within safe limits. Cheeses with LP addition exhibited lower BA levels, suggesting a modulating effect on their biosynthesis. Histamine concentrations were higher in raw milk cheeses with added cultures but remained well below hazardous levels. These findings suggest that incorporating either LP or LM strains is a promising strategy for enhancing the microbial safety and standardization of artisanal goat cheese while preserving its traditional characteristics.